A mega urban project and two competing accumulation strategies: negotiating discourses of the Songdo International Business District development. Issue 3 (June 2017) - Sonn, Jung Won; Shin, HaeRan; Park, Se Hoon
Abstract : For the understanding of the accumulation strategy behind a mega urban development project, the distinction should be made between the two different strategies of capital accumulation, which we term the rentextraction strategy (RES) and the socio-economic transformation of space strategy (STSS). This distinction is important because each is preferred by actors at different scales, thereby creating conflicts between them. Local actors are likely to prefer RES because its benefits mainly fall in the local area. National actors often prefer STSS because it symbolises state-level commitment to a business-friendly economic environment. Negotiation between these two strategies constitutes a major part of the formation of accumulation strategy. We test this theoretical prediction against the case of Songdo International Business District in South Korea. We find that the history of the project is consistent with our theoretical prediction.